Human-induced pluripotent stem cells-derived retinal pigmented epithelium, a new horizon for cells-based therapies for age-related macular degeneration - Samaneh Dehghan; Reza Mirshahi; Alireza Shoae-Hassani; Masood Naseripour (Stem Cell Research & Therapy, 2022)
Abstract Retinal pigment epithelium (RPE) degeneration is the hallmark of age-related macular degeneration (AMD). AMD, as one of the most common causes of irreversible visual impairment worldwide, remains in need of an appropriate approach to restore retinal function. Wet AMD, which is characterized by neovascular formation, can be stabilized by currently available therapies, including laser photocoagulation, photodynamic therapy, and intraocular injections of anti-VEFG (anti-vascular endothelial growth factor) therapy or a combination of these modalities. Unlike wet AMD, there is no effective therapy for progressive dry (non-neovascular) AMD. However, stem cell-based therapies, a part of regenerative medicine, have shown promising results for retinal degenerative diseases such as AMD. The goal of RPE cell therapy is to return the normal structure and function of the retina by re-establishing its interaction with photoreceptors, which is essential to vision. Considering the limited source of naturally occurring RPE cells, recent progress in stem cell research has allowed the generation of RPE cells from human pluripotent cells, both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSC). Since iPSCs face neither ethical arguments nor significant immunological considerations when compared to ESCs, they open a new horizon for cell therapy of AMD. The current study aims to discuss AMD, review the protocols for making human iPSCs-derived RPEs, and summarize recent developments in the field of iPSC-derived RPEs cell therapy.